DIVISION I: COMMISSION 7: CELESTIAL MECHANICS & DYNAMICAL ASTRONOMY. (13th August 2015) - Kneževic, Zoran; Morbidelli, Alessandro; Burns, Joseph; Athanssoula, Evangelia; Laskar, Jacques; Malhotra, Renu; Mikkola, Seppo; Peale, Stan; Roig, Fernando
Abstract : President of Commission 7 Zoran Knežević opened the business meeting at 18:40 and proposed the agenda which was accepted without change.